Has digital development achieved a synergistic effect of reducing energy intensity and improving carbon emission performance? evidence from China - Wang, Saige; Zhong, Honglin; Yang, Gang; Zhou, Anhua; Liu, Jing (Frontiers in Environmental Science, 2024)
The rapid growth of the Chinese economy has significantly escalated energy consumption and carbon emissions. The imperative to achieve synergies in energy conservation and carbon reduction has never been more pressing. Digital development presents promising avenues for addressing these challenges, making it crucial to investigate its impact on energy intensity (EI) and carbon emission performance (CEP). This study integrates the super efficiency epsilon-based measure (SE-EBM), mediation effect, and threshold effect models to assess the influence of digital development on EI and CEP using data from 267 cities across China from 2011 to 2019. Our findings demonstrate a notable 23.1% reduction in EI and an 18.5% improvement in CEP attributable to digital development. Moreover, our analysis underscores the pivotal role of technological innovation as a transformative conduit. Importantly, we identify significant threshold effects linked to economic development stages. This study not only enriches our understanding of pathways to energy conservation and carbon reduction but also provides compelling evidence supporting policies aimed at fostering and accelerating digital development initiatives.